2021
DOI: 10.1016/j.isci.2021.103412
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hsp90 inhibitor SNX-5422 attenuates SARS-CoV-2 replication and dampens inflammation in airway cells

Abstract: Highlights SNX-5422 inhibits SARS-CoV-2 replication in vitro at a high selectivity index Transcriptomic profile of human airway epithelial cells treated with SNX-5422 SNX-5422 dampens proinflammatory pathways associated with poor COVID outcomes SNX-5422 targets host factors crucial for SARS-CoV-2 replication

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 85 publications
3
17
0
Order By: Relevance
“…In human cell lines infected with SARS-CoV and SARS-CoV-2, HSP90 inhibition resulted in reduction of viral replication, which suggests its involvement in infection []. Taking into account recent studies pointing out HSP90 as a potential target in COVID-19 treatment [ 72 , 73 , 74 , 75 ], this finding especially supports the value of presented here results.…”
Section: Discussionsupporting
confidence: 92%
“…In human cell lines infected with SARS-CoV and SARS-CoV-2, HSP90 inhibition resulted in reduction of viral replication, which suggests its involvement in infection []. Taking into account recent studies pointing out HSP90 as a potential target in COVID-19 treatment [ 72 , 73 , 74 , 75 ], this finding especially supports the value of presented here results.…”
Section: Discussionsupporting
confidence: 92%
“…Wyler et al demonstrated that inhibition of Hsp90 activity by onalespib, ganetespib, or 17-AAG resulted in a reduction of both SARS-CoV-2 replication and expression of pro-inflammatory cytokines in primary human airway epithelial cells (22). Similar results were obtained by Goswami et al using the Hsp90 inhibitor SNX-5422 (23). In addition, in vitro experiments revealed inhibition of SARS-CoV-2 replication by the Hsp90 inhibitors 17-AAG and tanespimycin, respectively (24, 25).…”
Section: Hsp90/70 and Covid-19supporting
confidence: 52%
“…To explore the susceptibility of human iPS cell-derived podocytes to live SARS-CoV-2, podocytes were incubated with SARS-CoV-2 strain USA-WA1/2020 at MOI of 0.01, 0.1 or 1.0 for 1 h. All steps with live virus were strictly performed in Duke’s BSL3 facility following the guidelines provided by Duke University’s Biosafety committee and the CDC. The range of MOIs chosen was based on previously established models of infection kinetics ( Goswami et al, 2021 ). After 1 h incubation, cells were washed with PBS and then incubated with fresh culture medium for 24, 48 and 72 h ( Supplementary Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…We next performed plaque assays to measure the amount of infectious SARS-CoV-2 particles released from infected podocytes ( Supplementary Figures S1E–G , respectively). Ten-fold dilutions of each cell supernatant were assessed in duplicates as previously described ( Goswami et al, 2021 ). The number of plaque forming units (PFU) was significantly higher in the cells infected with MOI of 0.1 at 72 h.p.i compared to 24 and 48 h.p.i.…”
Section: Resultsmentioning
confidence: 99%